Genome of the enigmatic watering-pot shell and morphological adaptations for anchoring in sediment - Sigwart, Julia D.; Wong, Nur Leena W.S.; González, Vanessa Liz; Machado, Fabrizio Marcondes; Greve, Carola; Schell, Tilman; Chen, Zeyuan (BioMed Central, 2025)
Background: In this study, we present the first chromosome-scale genome of Verpa penis (Linnaeus, 1758), and the first for the bivalve clade Anomalodesmata. The present study has two separate foci. Primarily, we provide the genetic resource to bridge further studies from genome to phenome and propose hypotheses to guide future empirical investigations. Secondarily, based on morphology, we outline a conceptual exploration to address their adaptation. Watering-pot shells have been called “the weirdest bivalves” for their fused tubular shell resembling the spout of a watering can. This adventitious tube arose twice convergently in clavagelloidean bivalves. However, previous literature has never provided a convincing adaptive pathway. Results: The genome assembly of V. penis was about 507 Mb, with contig N50 of 5.33 Mb, and has 96.5% of sequences anchored onto 19 pseudochromosomes. Phylogenomic analyses of this new genome in context of other bivalves confirms the placement for Anomalodesmata as sister to the clade Imparidentia. Contrary to expectations from its highly modified body plan, there is no evidence of chromosome reduction compared to the ancestral karyotype of heterodont bivalves (1 N = 19). Drawing on established principles from engineering as well as morphology, the thought experiment about the adventitious tube seeks to extend current understanding by exploring parallels with other built structures. A new hypothesis explains one possible interpretation of the adaptive significance of this body form: it is potentially structurally optimised for vertical stability in relatively soft sediments, with parallels to the engineering principles of a suction anchor. Conclusions: While the conclusions presented here on morphological interpretations are theoretical, this serves as a foundation for further empirical validation and refinement. Our study offers new insights to a long-standing mystery in molluscan body forms and provides genomic resources that are relevant to understanding molluscan evolution, biomineralisation, and biomimetic design.